Correction: A study of forecasting tennis matches via the Glicko model. - Jack C Yue; Elizabeth P Chou; Ming-Hui Hsieh; Li-Chen Hsiao (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0266838.].